Age characteristics of first formers' readiness to musical upbringing at Primary school (Pedagogy of Higher and Secondary Education, 2006)
The issues of age peculiarities of the development of six year old children are brought up in the article. The physical м mental peculiarities are analyzed, the leaching techniques for singing of six year old students at Music lessons at Primary school.
Keywords: age-related peculiarities; physical and mental characteristics; musical abilities; teaching techniques for singing